Effects of food processing technology on valuable compounds in elderberry (Sambucus nigra L.) varieties - Szalóki-Dorkó, Lilla; Légrádi, Fleur; Abrankó, László; Stéger-Máté, Mónika (Acta Biologica Szegediensis, 2014)
Elderberry (Sambucus nigra L.) is a potential source of natural food colorants because of its high anthocyanin content. The aim of this work is to reveal which technology step has effect on the valuable components (total anthocyanins, total polyphenols) and on the color parameters in elderberry and in this regard to determine possible differences between elderberry varieties. Based on experiment results concentrate production steps have great effects on the studied parameters in case of two varieties especially in the heating and microfiltration steps but in different ratio. Polyphenolic compounds in ‘Samocco’ are more stable during the juice production than ‘Haschberg’. Color stability test revealed that in case of colored samples ‘Samocco’ had stronger color intensity in the foods/ models. These differences should be taken into account when selecting a certain variety for industrial utilization.